THE SYNERGY BETWEEN GASTRONOMY AND ACTIVE TOURISM AS INDICATORS OF SUSTAINABLE RURAL WELLNESS AND SPA DESTINATION DEVELOPMENT - SOKOBANJA CASE STUDY - Arsić, Martina; Vujko, Aleksandra; Nedeljković, Dragan (Economics of Agriculture, 2025)
This study investigated the relationship between recreation and gastronomy as key indicators of sustainable development in spa destinations. The research sought to answer two main questions: “What significance do recreation and active tourism hold for tourists?” and “What type of gastronomy attracts tourists to destinations?” The data from collected 243 respondents, comprising guests of the Sunce Hotel, Golden View Garni Hotel, and visitors to the Zelengora restaurant in Sokobanja, were analyzed using factor analysis. The authors conducted the research using two questionnaires. The findings of the first survey revealed a strong inclination to relaxation of both mind and body. Additionally, the results of the second survey indicated that a unique gastronomic experience is a significant motivator for tourists. Both indicators have a positive impact on tourists’ overall well-being and foster loyalty to the destination. In conclusion, active, gastronomic, wellness, and spa tourism have a beneficial influence on the tourist destination of Sokobanja. The study proposes a unique model that can be applied to all rural spa destinations.